(untitled) (Dermatology Reports, 2021)
A very rare variant of mammary Paget disease (MPD) is the pigmented MPD, first described in 1956. It is very difficult to distinguish this variant from melanoma both clinically and dermoscopically. The diagnosis is confirmed by histopathology and immunohistochemistry. Correct diagnosis is crucial for surgical treatment, which is different for these two diseases. We report the case of a 92-year-old woman, who presented an asymptomatic pigmented lesion of the right nipple and areola. The lesion was arisen for about 6 months and was suspected for melanoma because of clinical and dersmoscopic characteristics. Incisional biopsy revealed tumor cells, that proliferate in the major mammary ducts, and tumor cells in the overlying epidermis of the nipple, thus diagnosing pigmented mammary Paget disease. The patient underwent radical mastectomy.